Debt and Growth : Is There a Magic Threshold? - Pescatori, Andrea; Sandri, Damiano; Simon, John. (Washington, D.C. : International Monetary Fund, 2014)
Using a novel empirical approach and an extensive dataset developed by the Fiscal Affairs Department of the IMF, we find no evidence of any particular debt threshold above which medium-term growth prospects are dramatically compromised. Furthermore, we find the debt trajectory can be as important as the debt level in understanding future growth prospects, since countries with high but declining debt appear to grow equally as fast as countries with lower debt. Notwithstanding this, we find some evidence that higher debt is associated with a higher degree of output volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country Peer; Growth Rate; Growth; Sovereign Debt; WP; Japan